2018
DOI: 10.1186/s13045-018-0619-z
|View full text |Cite
|
Sign up to set email alerts
|

A cytoplasmic long noncoding RNA LINC00470 as a new AKT activator to mediate glioblastoma cell autophagy

Abstract: BackgroundDespite the overwhelming number of investigations on AKT, little is known about lncRNA on AKT regulation, especially in GBM cells.MethodsRNA-binding protein immunoprecipitation assay (RIP) and RNA pulldown were used to confirm the binding of LINC00470 and fused in sarcoma (FUS). Confocal imaging, co-immunoprecipitation (Co-IP) and GST pulldown assays were used to detect the interaction between FUS and AKT. EdU assay, CCK-8 assay, and intracranial xenograft assays were performed to demonstrate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 51 publications
2
60
0
Order By: Relevance
“…9 In our previous studies, we found that LINC00470 activated the AKT signalling pathway and promoted the tumour growth of intracranial transplantation mouse model with glioma. 10 However, the role and mechanism of LINC00470 in glioma must be further elucidated; in particular, it remains unclear whether LINC00470 affects the chemosensitivity of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…9 In our previous studies, we found that LINC00470 activated the AKT signalling pathway and promoted the tumour growth of intracranial transplantation mouse model with glioma. 10 However, the role and mechanism of LINC00470 in glioma must be further elucidated; in particular, it remains unclear whether LINC00470 affects the chemosensitivity of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…KCTD21-AS1, which promoted protein degradation and reduced cellular signaling, was associated with many diseases, including breast cancer [34] and obesity [35]. A study by Liu et al indicated that LINC00470 was up-regulated in glioblastoma cell and its high level expression was an unfavorable prognosis marker for astrocytoma patients [36]. Moreover, SNHG14, as a key lncRNA, facilitated the migration and invasion of clear cell renal cell carcinoma via sponging miR-203 and accelerate Neural Wiskott-Aldrich syndrome protein [37].…”
Section: Discussionmentioning
confidence: 99%
“…Multitudes of studies have demonstrated the importance of PI3K in the activation of AKT, while evidence suggests that AKT activation can proceed by the PI3K independent manner [27]. Several lncRNAs (LINK-A, lncRNA OIP5-AS1, MALAT1 and LINC00470) promote the over activation of AKT signaling [28][29][30][31]. In this study, Western blot analysis results con rmed AKT activity was apparently suppressed in U87 cells but slightly in U251 cells with LINC00663 knockdown, without affecting mTOR in the AKT pathway, which was worthy of attention in the future.…”
Section: Discussionmentioning
confidence: 99%